Development of android-based learning media applications on elements periodic system topics - Anisa Pradila; Fajriah Azra (Jurnal Pijar Mipa, 2022)
This study aims to develop android-based learning media applications and determine the level of validity. This research was designed using the Plomp development model, which consists of 3 stages: the preliminary research stage, the development stage or prototyping, and the assessment stage. In this study, the authors limit the research carried out to the development stage or prototype, which produces prototype III. The development of this android-based application is expected to assist teachers in overcoming obstacles in making learning media and can be used as one of the learning media that can help students in learning, especially on the material of the periodic system of elements. Nine validators carried out the validation test of the learning media application: six content experts (Padang State University lecturers and teachers of SMAN 12 Padang) and three media experts (Lecturer of Engineering Padang State University). The data obtained from the validator was then analyzed using Aiken's V. The product validation test results had an index of 0.877 from content experts and 0.955 from media experts in the valid category. Thus, based on the validation test results, the Android-based learning media application on the developed periodic system material is valid.